Overview of the current situation and prospects of using rocket fuels - Трофімов, Ігор Леонідович; Бойченко, Сергій Валерійович; Ландарь, Іван Олексійович (Science-based technologies, 2020)
In the article discusses the current state and prospects for the use of rocket fuels in Ukraine. The main purpose of the work was analyze the range of brands of modern rocket fuels suitable for use in Ukraine, analysis of basic physical, chemical and operational properties, technical requirements for rocket fuel quality, problems of refueling infrastructure and cleanliness of rocket fuels.In addition to the ban on the use of highly toxic nitric acid-based rocket fuels in Ukraine, there is a problem associated with the lack of production of its own hydrocarbon rocket fuels based on oil. In general, this has led to the fact that today in Ukraine there is an acute problem with the provision of rocket fuels for spacecraft and rocket carriers of Ukrainian production.The constant attention to the problem of the quality of aviation and rocket fuels is caused by many factors. At high levels of purity of fuels safety of flights is guaranteed, reliability is provided, technical resource of units of systems increases therefore expenses for achievement and maintenance of necessary level of purity of fuel and working liquids are quite justified. The article presents the classification of liquid rocket fuels based on their component composition and chemical structure.The requirements to energy, kinetic, operational characteristics, ecological and economic properties of liquid rocket fuels (LRF) are given. It is established that given the far unsatisfactory environmental situation in Ukraine, the use of kerosene as a rocket fuel is relevant for our country today in comparison with heptyl rocket fuel. Jet fuels T-1, T-6, T-8B are well suited for domestic space production, but they are not produced in Ukraine, and their purchase in Russia is currently impossible for a number of reasons. Comparative analysis has shown that the American liquid rocket fuel RP-1 in most respects is an analogue of jet fuel T-1 and T-6 and can be used for rocket carriers of Ukrainian production. Today in Ukraine the problem of development of normative documents on quality control of LRF during their storage and exploitation is not solved. In particular, there is no clear regulatory documentation for the process of refueling LRF when the temperature is low. Unlike aviation fuels, there are no regulations and other regulatory documents on the content of free and dissolved water and mechanical impurities in the LRF. One of the promising areas of rocket fuel use is the use of fuel cells. The results of the research can be applied in the field of spacecraft operation, as well as refueling infrastructure and cleanliness of rocket fuels. The results of the article can be used by chemical experts, specialists in the field of operation of refueling and storage of LRF